Matching contours in images using curvature information - Francisco Paulo Marques de Oliveira (2008)
The work here described consists in searching for the optimum global matching between contours of two objects represented in images, which are sampled by equal or different number of points. Thus, to determine the optimum global matching between the points of two contours, it is used curvature information, that is totally invariant to rigid transformations. For the case of contours sampled by different numbers of points, two approaches are proposed to exclude, from the matching process, the additional points. In the last section of this paper, a method for the determination of the rigid transformation associated to two contours that is based in the same solution considered in our matching process is also described.